Analysis of differential alternative splicing at the gene isoform and genomic levels using Cufflinks, Miso, and rMats – an example of ANO7 in prostate cancer - Ennejmy, Mohammed (My University, 2020)
The diagnosis and treatment of prostate cancer (PCa) are the most extensively researched fields in Urology. Studying gene expression profiling in PCa as well as in other types of cancer necessitates the investigation of differential expression at the transcript isoforms level rather than the gene level. With the next-generation sequencing (NGS) technology, ultra-deep RNA sequencing (RNA-Seq) has become a powerful approach. It enables researchers to study biological systems and transcriptional state of the cell at an unprecedented level of detail for genome-wide analysis of pre-mRNA alternative splicing. Hence, genetic factors are viable candidates for biomarkers of PCa progression. Moreover, current studies have shown that inherited and acquired changes in pre-mRNA splicing are likely to play a major role in cancer development, and many cancer-associated genes are regulated through alternative splicing 33. Therefore, understanding the process of aberrant splicing and the detailed characterization of splice variants may prove crucial to our understanding of malignant transformation as splice variants that are found predominantly in tumors could have clear diagnostic value and provide potential drug targets. Therefore, signature mRNA isoforms can serve as exceptional biomarkers for PCa diagnosis and prognosis 12. Additionally, with recent advances in high-throughput RNA-Seq technology, the ability to understand the complexity of transcriptomes has been significantly enhanced. In this thesis, the aim was to investigate the association between the rs148609049 SNP and differential alternative splicing both at the ANO7 isoform and genomic levels by making use of alternative splicing tools Cufflinks, Miso, and rMats.
Keywords: Alternative splicing, Prostate Cancer, Isoform expression, Cufflinks, rMats, Miso, ANO7